Adsorption and inhibitive properties of some new Mannich bases of Isatin derivatives on corrosion of mild steel in acidic media - Ahamad I.; Prasad R.; Quraishi M.A. (My University, 2025)
Adsorption of four derivatives of piperidinylmethylindoline-2-one on mild steel surface in 1 M HCl solution and its corrosion inhibition properties has been studied by a series of techniques, such as polarization, electrochemical impedance spectroscopy (EIS), weight loss and quantum chemical calculation methods. The values of activation energy (Ea) for mild steel corrosion and various thermodynamic parameters were calculated and discussed. Potentiodynamic polarization measurements showed that all inhibitors are mixed type. The degree of surface coverage was determined by using weight loss measurements and it was found that adsorption process of studied inhibitors on mild steel surface obeys Langmuir adsorption isotherm. © 2010 Elsevier Ltd. All rights reserved.